Impactos econômicos do Programa Minha Casa, Minha Vida de 2009 a 2021 - Welter, Amauri (2025)
The Minha Casa, Minha Vida (MCMV) Program, one of Brazil’s main housing policies, is widely recognized for its role in socioeconomic development. However, its direct economic effects – especially at the state level – still require further investigation. This study analyzes the economic impacts of the MCMV, between 2009 and 2021, in Brazilian federative units, considering variables such as production, employment, income, and tax collection. To this end, the input-output analysis methodology is applied, focusing on state multipliers in 2010, 2015, and 2021. The results reveal significant variations between states in terms of the program’s impact, highlighting its relevance as a regional economic driver. In addition, it is found that there is no direct correlation between the amounts transferred by the program and the reduction of the housing deficit. This dissociation indicates that public resources although beneficial form an economic point of view, could be allocated more strategically to achieve social objectives more effectively. In this way, in addition to offering a quantitative diagnosis of the impacts of MCMV, the research, contributes to the discussion on the allocative efficiency of public policies in Brazil. The results also provide important support for improving the management of housing programs, as well as for future studies that seek to evaluate the economic effect of other public policies aimed at regional development.